(untitled) (Fiep Bulletin - online, 2014)
The Burnout Syndrome (BS) is a result of a gradual process of exhaustion, generating burnout, affecting health professionals in particular the nursing staff. An evaluation scale of BS was applied to the adult ICU nursing staff at a hospital of Foz do Iguaçu, Brazil, in the three work shifts in order to identify emotional changes of respondents. The sample consisted of 04 nurses and 24 assistant nurses distributed into morning, afternoon and evening shifts. The Maslach Burnout Inventory was applied. After collection, data were submitted to descriptive analysis using the SPSS-14 software. The results showed that 67% of workers are emotionally exhausted and 85% of them treat patients as object. It was concluded that the health professionals surveyed have BS, requiring an improvement in the work organization in order to make the work environment more comfortable, safer, and healthier.